2021
DOI: 10.3390/electronics10182260
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies for Innovative Mental Health Rehabilitation

Abstract: Schizophrenia is a chronic mental illness, characterized by the loss of the notion of reality, failing to distinguish it from the imaginary. It affects the patient in life’s major areas, such as work, interpersonal relationships, or self-care, and the usual treatment is performed with the help of anti-psychotic medication, which targets primarily the hallucinations, delirium, etc. Other symptoms, such as the decreased emotional expression or avolition, require a multidisciplinary approach, including psychophar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Virtual games as an auxiliary tool for rehabilitation can be a very interesting path for the future to benefit people diagnosed on the schizophrenia spectrum [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual games as an auxiliary tool for rehabilitation can be a very interesting path for the future to benefit people diagnosed on the schizophrenia spectrum [10].…”
Section: Discussionmentioning
confidence: 99%
“…In psychiatry in particular, traditional treatment tools have been limited mainly to psychotherapy and medication. Rehabilitation supported by digital technologies has thus emerged as a solution to support health professionals by providing high-intensity, repetitive, and task-specific exercises to improve the rehabilitation process [10]. VR has already been applied to the treatment of various pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have demonstrated its effectiveness in the treatment of post-traumatic stress disorder, anxiety disorder, and specific phobias. Actually, rehabilitation supported by digital technologies has thus emerged as a solution to support health professionals by providing high-intensity, repetitive, and task-specific exercises to improve the rehabilitation process [23].…”
Section: Mental Health -Vr Applicationsmentioning
confidence: 99%
“…According to the US Food and Drug Administration, digital health technologies “use computing platforms, connectivity, software, and sensors for health care and related uses” [ 10 ]. Digital health technology has been deemed valuable and efficient in supporting health care providers and family caregivers in different populations, such as children with special health care needs [ 11 ], patients undergoing hematopoietic cell transplantation [ 12 ], and patients with Parkinson disease [ 13 ], as well as patients requiring cardiovascular care [ 14 ], pulmonary rehabilitation [ 15 , 16 ], mental health rehabilitation [ 17 ], and cognitive rehabilitation [ 18 ]. Digital health technology faces challenges at individual and system levels, such as lack of presence and in-person contact [ 19 ] as well as ethics and data governance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%